Pekan folk overjoyed over newly-refurbished homes - UMP, PNC (The New Straits Times Press (M) Bhd., 2017)
PEKAN: Fatimah Abdullah's voice choked with emotion as she spoke about her newly-refurbished single-storey house at Kampung Kuala Pahang here yesterday.